TEENAGE SCHOOLCHILDREN'S TIME PERSPECTIVE AS A PSYCHOLOGICAL AND PEDAGOGICAL ISSUE - Svetlana A. Vasyura; Natalia I. Iogolevich (National Research Mordova State University, 2017)
Introduction: the article deals with human psychological time. Though there are observational studies focused on this topic, the psychological, pedagogical, and age-related aspects of this issue require more attention. The development of the human time perspective during the teenage period is in the authors' field of view. The aim of the study is to identify main characteristics of teenagers' time perspective depending on their generalized anxiety level and use them as a basis for working out a psychological and pedagogical support model for teenagers' time perspective development. Materials and Methods: to study specific aspects of the time perspective formed by teenagers having various generalised anxiety levels, the psychodiagnostic methods were used: a trait anxiety scale for 10-16 years old students by A. M. Prikhozhan; anxiety research methods by C. D. Spielberger and Yu. L. Khanina; and the methods enabling diagnostics of the attitude to past, present, and future by A. M. Prikhozhan. The mathematical statistics methods were applied: Mann-Whitney U Test, Spearman's rank correlation coefficient and Fisher's angular transformation φ-index. Results: the specific aspects of the time perspective have been revealed; its interrelation with the various levels of the teenage schoolchildren's generalised anxiety levels has been established. Based on the obtained research results, a psychological and pedagogical support model of teenage schoolchildren's time perspective development was elaborated. The main components of this model have been introduced. Discussion and Conclusions: the time perspective of the teenagers having a higher anxiety level is inconsistent. It is characterised by a negative attitude to past, present and future. The psychological and pedagogical support to teenage schoolchildren in terms of their time perspective development will provide: psychological and pedagogical support to reduce teenagers' personal anxiety and correct unfavourable alternatives of their life perspective appreciation and facilitating teenage personal development. Practical importance of the study is that a psychological and pedagogical support model has been worked out. The model implementation makes it possible to integrate the efforts of teachers, psychologists and parents to create the psychological conditions for the teenagers' personality development..